2017
DOI: 10.1007/s00779-017-1081-6
|View full text |Cite|
|
Sign up to set email alerts
|

Man-in-the-middle attacks on Secure Simple Pairing in Bluetooth standard V5.0 and its countermeasure

Abstract: Bluetooth devices are widely employed in the home network systems. It is important to secure the home members' Bluetooth devices, because they always store and transmit personal sensitive information. In the Bluetooth standard, Secure Simple Pairing (SSP) is an essential security mechanism for Bluetooth devices. We examine the security of SSP in the recent Bluetooth standard V5.0. The passkey entry association model in SSP is analyzed under the man-in-the-middle (MITM) attacks. Our contribution is twofold. (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…Hypponen and Haataja (2007), made a research on secure Bluetooth communication and showed their developed system was capable of preventing MITM attack (Hypponen & Haataja, 2007). Sun et al, 2018 andSaif et al, 2018; made similar type of researches on updated version of Bluetooth networks security and discussed about new techniques to prevent MITM in two party's communication (Sun et al, 2018;Saif et al, 2018). Ouafi et al (2008), Callegati et al (2009), Joshi et al, (2009), Desmedt, (2011 and Sounthiraraj et al, (2014) conducted researches about HTTP security and those researches found MITM as a very serious threat and those also discussed about the prevention techniques (Ouafi et al, 2008;Callegati et al, 2009;Joshi et al, 2009;Desmedt, 2011;Sounthiraraj et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypponen and Haataja (2007), made a research on secure Bluetooth communication and showed their developed system was capable of preventing MITM attack (Hypponen & Haataja, 2007). Sun et al, 2018 andSaif et al, 2018; made similar type of researches on updated version of Bluetooth networks security and discussed about new techniques to prevent MITM in two party's communication (Sun et al, 2018;Saif et al, 2018). Ouafi et al (2008), Callegati et al (2009), Joshi et al, (2009), Desmedt, (2011 and Sounthiraraj et al, (2014) conducted researches about HTTP security and those researches found MITM as a very serious threat and those also discussed about the prevention techniques (Ouafi et al, 2008;Callegati et al, 2009;Joshi et al, 2009;Desmedt, 2011;Sounthiraraj et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Effective MITM execution has two distinct stages: interception and decryption; which involves being within physical closeness to the intended target, and another that exclusive involves malware, known as a man-in-the-browser (MITB) attack. With a conventional MITM attack, the attacker needs access to an unsecured, or ineffectively anchored Wi-Fi switch (Li et al, 2017;Rahim, 2017;Fei et al, 2018;Howell et al, 2018;Sun et al, 2018). These sorts of associations are by and large found out in the open territories with free Wi-Fi hotspots, and even in a few people's homes.…”
Section: Progression Of 'Man-in-the-middle-attack'mentioning
confidence: 99%
See 1 more Smart Citation
“…The stages involve physical closeness to the intended target, and another that exclusive involves malware, known as a man-in-the-browser (MITB) attack. With a conventional MITM attack, the attacker needs access to an unsecured, or ineffectively anchored Wi-Fi switch (Sun et al, 2018). These sorts of associations are by and large found out in the open territories with free Wi-Fi hotspots, and even in a few people's homes.…”
Section: Progress Of Mitmmentioning
confidence: 99%
“…Typically, sensor devices can communicate with smartphones by key pairing using a Bluetooth protocol, and communicate with MCUs by sharing radio pipe addresses [20]. These typical approaches do not protect from malicious sensor attacks, or they do not recognize the issues that might occur in the sensor device side [21,22].…”
Section: Wireless Network Securitymentioning
confidence: 99%